Karakteristik karet ebonit yang dibuat dengan berbagai variasi rasio RSS I/Riklim dan jumlah belerang - Setyowati, Penny; Rahayu, Sutarti; Supriyanto, Supriyanto (Majalah Kulit, Karet, dan Plastik, 2004)
The aim of the research was to study the influence of utilization of sulphur and reclaim rubber on the characteristics of ebonite rubber, and also to determine the optimum utilization of reclaim rubber and sulphur which yield good physical properties. Ebonite rubber was made by special natural rubber of RSS I (Ribbed Smoke Sheet I) mixed with reclaimed rubber at ratio 80/20, 70/30 and 60/40 part hundred rubber/part hundred rubber (phr/phr) and utilization of sulphur 30, 40, and 50 phr and also additives respectively. Mixing was done by using open mill, and vulcanization was conducted at early temperature 1200C for 2 hours, and it was continued by post curing at temperature 1500C for 2 hours. The physical properties such as tensile strength, elongation at break, D shore hardness, and izod impact of ebonite rubber vulcanized were determined. The result indicated that characteristics of ebonite rubber was significantly influenced by the amount of added sulphur and 40 phr reclaim rubber or at ratio of RSS I to reclaim rubber 60 to 40 phr/phr. However, the physical properties of ebonite rubber was able to meet the standard quality of group 2 regarding to Classification Hard Rubber issued by ASTM D 2135.    Key words : Ebonite, reclaim, sulphur, natural rubber. Penelitian ini bertujuan untuk mempelajari pengaruh penggunaan belerang dan karet riklim terhadap sifat karet ebonite serta menentukan jumlah penggunaan karet riklim dan belerang yang optimum yang menghasilkan sifat-sifat fisik yang baik. Karet ebonite dibuat dari karet alam RSS I yang dicampur denga karet riklim pada perbandingan berturut-turut 80/20, 70/30 dan 60/40 phr/phr serta penggunaan belerang berturut-turut 30, 40 dan 50 phr dengan bahan-bahan pembantu dalam jumlah tertentu. Pencampuran dilakukan dengan alat open mill dan vulkanisasi dilakukan pada suhu awal 1200C selama 2 jam, dilanjutkan post curing pada suhu 1500C selama 2 jam. Selanjutnya karet ebonite diuji sifat fisikanya meliputi tegangan putus, perpanjangan putus, kekerasan shore D dan pukul takik. Dari hasil yang diperoleh memperlihatkan bahwa penambahan belerang dan karet riklim berpengaruh secara nyata. Nilai optimum dicapai pada penggunaan belerang 30 phr dan karet riklim 40 phr atau pada perbandingan RSS I / karet riklim 60/40 phr/phr. Sifat-sifat fisik karet ebonite yang dihasilkan masuk standar kualitas kelompok 2 dalam klasifikasi hard rubber versi ASTM D 2135.  Kata Kunci  : ebonit, riklim, belerang, karet alam.